A Systematic Review of Teacher-Mediated Interventions to Improve the Mathematical Performance of Students with Emotional and Behavioral Disorders. Issue 2 (14th March 2020) - Peltier, Corey; Vannest, Kimberly J.; Morin, Kristi L.; Sinclair, Tracy E.; Sallese, Mary Rose
ABSTRACT: Students with emotional and behavioral disorders (EBD) demonstrate poor academic outcomes, particularly in mathematics. Student-mediated interventions (e.g., self-management, self-monitoring, self-instruction) are replete in the intervention literature base for students with EBD. However, teacher-mediated interventions have been examined less frequently. The goal of this project was to examine the literature on teacher-mediated interventions to improve the mathematical performance of students with EBD to identify what is known and gaps that need to be filled. A total of 17 studies including 47 students met inclusion criteria; however, only seven studies including 17 students met the What Works Clearinghouse (WWC) Pilot Single-Case Design Standards with or without reservations. Using the WWC Evidence Standards, six studies demonstrated moderate evidence of effect and one study demonstrated weak evidence. The omnibus Tau-U was 72% (CI95 62–82%), representing data from the seven studies that met the WWC Design Standards . We calculated the between-case standardized mean difference (BC-SMD) for four studies that met assumptions; the effect sizes ranged from 3.48 to 0.45. Implications for research and practice are discussed.